Peran Pekerja Sosial Dalam Pemberdayaan Disabilitas Di Sentra Budi Perkasa Kota Palembang - M. Dicky Wahyudi; Eni Muridiati; Hartika Utami Fitri (ScidacPlus, 2023)
Empowerment is a way to provide a foundation in the main foundation for strengthening a person to be able to have skills and be able to meet their own needs independently. So empowerment is an important thing to do, including people with disabilities. This research is to analyze the role of social workers in empowering people with disabilities. The purpose of this research is to find out the programs run from social workers as facilitators in empowering people with disabilities, the process of guiding disabilities carried out by social workers and the impact on independence for people with disabilities at Sentra Budi Perkasa Palembang City. This research uses an empowerment theory approach from Robert Rappaport which says that empowerment in practice, is to train or make people with disabilities independent. This research is a qualitative research using descriptive method. The paradigm used is postpositivism, because it is to assess an object with facts in the field. Data collection was carried out using observation, interview and documentation techniques. Data analysis uses logical interpretation by reducing data obtained from observations to select and simplify those related to the context of Islamic community development. Based on the results of the research conducted, the empowerment carried out by Sentra Budi Perkasa Palembang City has a therapy program which includes physical therapy such as gymnastics and healthy walking, there is also music therapy, there are vocational and psychosocial programs to train habituation to the outside world. The empowerment process to empower is assisted by other professions such as psychologists, nurses, instructors, and even religious experts. In addition, the process in empowerment also goes through several stages, one of which is a case conference to find out the identity and background of people with problems. The impact of empowerment is the ability to care for oneself, maintain one's emotional self, and be able to interact with the environment. In general, this research can be concluded that social workers in empowering persons with disabilities play a very important role.